Intergenerational Support from Adult Children on Cognitive Function in Chinese Older Adults: The Chain Mediating Role of Life Satisfaction and Depression - Xia, Li; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
Against China’s rapid aging and cognitive decline concerns, this study explores intergenerational support’s role in older adults’ cognitive health. While family support is central to Chinese eldercare, whether life satisfaction and depressive symptoms mediate this link—especially across urban-rural areas—remains unclear. Data from the nationally representative CHARLS 2020 dataset (n=3,136, aged ≥60). Pearson correlations, PROCESS macro (5,000 bootstraps), and propensity score matching (PSM) was used to balance urban-rural covariates and test mediation heterogeneity. In this sample, intergenerational support correlated positively with cognitive function (r=0.123, p<0.01) and life satisfaction (r=0.064, p<0.01), and negatively with depressive symptoms (r=-0.129, p<0.01). Life satisfaction inversely linked to depression (r=-0.275), which associated with poorer cognition (r=-0.275, p<0.01). Regression showed direct effects of support on cognition (β=0.166, p<0.001), with stronger indirect effects through depressive symptoms (β=0.021) than life satisfaction (β=0.015). Serial mediation (support→satisfaction→depression→cognition) was significant (β=0.013). Depression-mediated effects were marginally stronger in rural subgroups (β=0.082) than urban subgroups (β=0.076). Intergenerational adult children’s support can effectively promote cognitive health among older adults by enhancing life satisfaction and alleviating depression. Life satisfaction and depressive symptoms act as key mediators in this process.